Essential newborn care practices in selected public health facilities using observation of 2603 normal deliveries in Uttar Pradesh, India - James Blanchard; Marissa L Becker; Ties Boerma; Ravi Prakash; Shajy Isac; Bidyadhar Dehury; Banadakoppa Manjappa Ramesh; Vasanthakumar Namasivayam; John Anthony; Nihal Hasan; Prakash P Javalkar (BMJ Global Health)
Introduction Essential newborn care (ENBC) practices are recommended for all births to improve neonatal survival. This paper aims to understand the facility-level variations and factors associated with the essential newborn care practices by providers in higher-level public health facilities in 25 high priority districts (HPDs) of Uttar Pradesh (UP).Methods We used observational cross-sectional quantitative data from 48 selected public health facilities (23 district hospitals (DH) and 25 community health centres (CHC)—first referral units (FRU)) implemented in 25 HPDs of UP from February 2020 to May 2021. We defined ENBC practice as both cord care and initiation of breastfeeding within 1 hour of birth were practiced in normal deliveries by the staff nurse. Descriptive analysis was done based on data from 2603 newborns attended by 318 providers. A stratified analysis was done by DH and CHC-FRU.Results Overall, essential newborn care was practiced among 26.1% of the newborns (26.2% in DH and 35.0% in CHC-FRU). The ENBC practice varied across facilities from 3.0% to 64.1% in DH and from 0% to 91.0% in CHC-FRU. The ENBC practice was about 2.3 times higher in facilities with a high level of skill and knowledge of the providers (39.0%) compared with the facilities with a low level of skill and knowledge (16.9%). Similar patterns of association between providers’ skills and knowledge of ENBC practices were observed in DH and CHC-FRU.Conclusion Skill and knowledge on ENBC components are significantly associated with the clinical practices of providers, with a high level of variability across facilities. This suggests a focused facility-based assessment and enhancement of the clinical competencies of the providers to improve the quality of care in public health facilities in UP.